Research observatory of the Micaela Bastidas National University of Apurimac - Zavala Huamaní, Brayan Renzo (2021)
The shortcomings found in the Vice Rectorate of Research of the UNAMBA was about the organization of information; the progress, status of thesis projects and final research reports of undergraduate students and teachers.  The objective of the research is to monitor the research projects produced at UNAMBA through the development of a web application (https://observatorio.unamba.edu.pe), the web application was developed mainly with technologies such as: Laravel, one of the most widely used PHP backend framework currently used, capable of facilitating an orderly, modular, secure and scalable development. Vue.js, a javascript-based frontend framework that ensures scalability through its progressive approach and orientation to the use of web components. Finally, it is worth mentioning the implementation of user authenti-cation methods through Google, Microsoft and Github services that facilitate au-thentication and a higher level of security with the use of a double authentication factor. As conclusive information, after the implementation of this thesis, it was determined that it has been possible to improve the monitoring of teaching re-search projects and undergraduate theses by more than 50%.